2023
DOI: 10.3389/fninf.2022.1056068
|View full text |Cite
|
Sign up to set email alerts
|

2.5D and 3D segmentation of brain metastases with deep learning on multinational MRI data

Abstract: IntroductionManagement of patients with brain metastases is often based on manual lesion detection and segmentation by an expert reader. This is a time- and labor-intensive process, and to that end, this work proposes an end-to-end deep learning segmentation network for a varying number of available MRI available sequences.MethodsWe adapt and evaluate a 2.5D and a 3D convolution neural network trained and tested on a retrospective multinational study from two independent centers, in addition, nnU-Net was adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…While earlier studies demonstrated high sensitivity in the detection of BMs, surpassing 80%, they were accompanied by a significant number of FPs and, consequently, exhibited low precision, as indicated in Table 5 (7,10,28,29). Subsequent research, incorporating multiple modalities, showed improved performance with sensitivities ranging from 82% to 100% and reducing the FP rate to between 0.6 and 1.5 per scan (6,8,30).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…While earlier studies demonstrated high sensitivity in the detection of BMs, surpassing 80%, they were accompanied by a significant number of FPs and, consequently, exhibited low precision, as indicated in Table 5 (7,10,28,29). Subsequent research, incorporating multiple modalities, showed improved performance with sensitivities ranging from 82% to 100% and reducing the FP rate to between 0.6 and 1.5 per scan (6,8,30).…”
Section: Discussionmentioning
confidence: 95%
“…While earlier studies demonstrated high sensitivity in the detection of BMs, surpassing 80%, they were accompanied by a significant number of FPs and, consequently, exhibited low precision, as indicated in Table 5 ( 7 , 10 , 28 , 29 ). Subsequent research, incorporating multiple modalities, showed improved performance with sensitivities ranging from 82% to 100% and reducing the FP rate to between 0.6 and 1.5 per scan ( 6 , 8 , 30 ). Notably, a recent study, utilizing a single modality, introduced a novel loss function and integrated temporal prior information, achieving exceptional results (sensitivity: 84%; precision: 99%; FP rate: 1) ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, deep learning (DL) models have been shown to be a valuable technique in radiology. Besides using DL for detection and segmentation intracranial abnormalities in brain images [17][18], there are also DL models for predictions from input images DL methods have also been used in MRP. There are commercial MRP software that have built-in automated AIF and VOF selection tools that utilize DL [21].…”
Section: Deconvolution Methods Require the Selection Of Two Vascular ...mentioning
confidence: 99%
“…for the automatic detection and segmentation of BMs from T1 MRI [2,3], T1 and CT [4], multiple T1s and FLAIR [5], using standard 2D, 2.5D and 3D Deep Learning (DL) models.…”
Section: Automated Brain Metastases Segmentation Several Work Have Re...mentioning
confidence: 99%